Burden and Determinants of Anemia among Under-Five Children in Africa: Systematic Review and Meta-Analysis - Sisay Eshete Tadesse; Aregash Abebayehu Zerga; Tefera Chane Mekonnen; Abay Woday Tadesse; Fozia Mohammed Hussien; Yitbarek Wasihun Feleke; Melaku Yalew Anagaw; Fanos Yeshanew Ayele (Anemia)
Introduction. Globally, anemia among under-five children is a serious public health problem. Even if there are pocket studies here and there, there is limited evidence on the pooled prevalence of anemia among under-five children in Africa. Therefore, the aim of this study was to determine the pooled prevalence and determinants of anemia. Methods and Analysis. This systematic review and meta-analysis was done following the PRISMA guidelines. A comprehensive search was made in PubMed/MEDLINE, Cochrane Library, HINARI, and Ethiopian Journal of Health Development for studies published since 2009. It was supplemented with Google Scholar search. Study selection, data extraction, and quality of studies were assessed by eight reviewers. The Cochrane Q test and I2 test statistic were used to test the heterogeneity of studies. A random-effects model of DerSimonian-Laird method was used. Result. A total of 37 articles were included in this systematic review and meta-analysis. The pooled prevalence of anemia among under-five children in Africa was 59% (95% CI: 55, 63). Being female (AOR = 0.71; 95% CI: 0.57, 0.87), maternal education (AOR = 1.47; 95% CI: 1.31, 1.66), residence (AOR = 0.80; 95% CI: 0.67, 0.95), and family size (AOR = 0.93; 95% CI: 0.89, 0.98) were the determinants of anemia among African under-five children. Conclusion and Recommendation. This pooled study revealed that anemia was a severe public health problem. Sex, maternal education, residence, and family size were the determinants of anemia. Therefore, anemia prevention strategy should include sex consideration, educating mothers through youth education, area specific intervention, and encouraging birth spacing.